Optimizing the Role of Economic Growth, Regional Original Income, and Revenue Sharing Funds in Increasing the Human Development Index in Indonesia - Rahadi Nugroho; Vissia Dewi Haptari; Ari Mulianta Ginting; Adhi Prasetyo Satryo Wibowo (Sean Institute, 2025)
There is still a gap between regions at the HDI level in Indonesia. Economic Growth, Regional Original Income, and Revenue Sharing Funds influence HDI. This study aims to analyse the increase in HDI associated with economic growth, regional original income, and profit-sharing funds. This study is quantitative research with secondary data from all provinces in Indonesia from 2017 to 2022. The dependent variable in this study is the Human Development Index. The independent variables in this study are the economic growth rate, regional original income and revenue sharing funds. Data on the Human Development Index and economic growth were obtained from the Central Statistics Agency. Meanwhile, the Directorate General of Financial Balance, Ministry of Finance, obtained the data on Regional Original Revenue and profit-sharing funds. The results of negative coefficients on economic growth variables and positive coefficients on Regional Original Income and Revenue Sharing Funds indicate that government intervention has a positive and significant effect on the Human Development Index in Indonesia.